El cuerpo, territorio de significación en las culturas en globalización (2005)
ABSTRACT: This rehearsal approaches, from the mark of the reflexive modernity, the thematic of the body in the system world, which is crossed for the globalization processes and its consequent one, territorial demarcation. In the mediation of these two circumstances they settle the local corporal practices in resistance to the media and their potential to normalize or to generalize.